La Paloma encuentra un perro caliente! - Willems, Mo; Campoy, F. Isabel (New York Hyperion Books for Children, 2011)
Pigeon learns about sharing when a curious duckling keeps asking questions about the hot dog Pigeon has found.
La Paloma aprende del compartir cuando un pato curioso sigue haciendole preguntas acerca del perro caliente la Paloma ha encontrado.
Accelerated Reader
Keywords: Pigeons -- Juvenile fiction; Ducklings -- Juvenile fiction; Sharing -- Juvenile fiction; Palomas -- Novela juvenil; Patitos -- Novela juvenil; Compartir -- Novela juvenil